2010
DOI: 10.1111/j.1365-2826.2010.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphic Effects of Leptin on the Circadian and Hypocretinergic Systems of Mice

Abstract: The hormone leptin controls food intake and body weight through its receptor in the hypothalamus, and may modulate physiological functions such as reproduction, sleep or circadian timing. In the present study, the effects of leptin on the resetting of the circadian clock, the hypothalamic suprachiasmatic nucleus (SCN) and on the activity of the hypocretinergic system were examined in vivo, with comparative analysis between male and female mice. A single leptin injection (5 mg/kg) at both the onset and offset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 58 publications
0
32
1
Order By: Relevance
“…As the circadian clock in the hypothalamus suprachiasmatic nuclei (SCN) controls rhythms of locomotor activity and this brain area has been shown to have leptin receptors (Guan et al 1997, Yi et al 2006, our results suggest that a leptin antagonist may counteract the effect of leptin on the SCN clock. Indeed, it has recently been shown that leptin potentiated the phase-shifting effect of a 30-min light pulse on behavioral rhythms during the late subjective night in female mice (Mendoza et al 2011). In contrast to our results, it was found that a 2-week chronic exposure to a physiological dose of leptin (100 mg/kg per day) decreased locomotor activity (Mendoza et al 2011).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…As the circadian clock in the hypothalamus suprachiasmatic nuclei (SCN) controls rhythms of locomotor activity and this brain area has been shown to have leptin receptors (Guan et al 1997, Yi et al 2006, our results suggest that a leptin antagonist may counteract the effect of leptin on the SCN clock. Indeed, it has recently been shown that leptin potentiated the phase-shifting effect of a 30-min light pulse on behavioral rhythms during the late subjective night in female mice (Mendoza et al 2011). In contrast to our results, it was found that a 2-week chronic exposure to a physiological dose of leptin (100 mg/kg per day) decreased locomotor activity (Mendoza et al 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, it has recently been shown that leptin potentiated the phase-shifting effect of a 30-min light pulse on behavioral rhythms during the late subjective night in female mice (Mendoza et al 2011). In contrast to our results, it was found that a 2-week chronic exposure to a physiological dose of leptin (100 mg/kg per day) decreased locomotor activity (Mendoza et al 2011). As obesity itself has been shown to also affect locomotor activity (Kohsaka et al 2007, it is possible that leptin resistance, a characteristic of obesity, is the reason for the disrupted locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…; Prosser & Bergeron 2003, Inyushkin et al 2009). In vivo experiments show that leptin injection potentiates behavioural light-resetting in mice, which is accompanied by a higher induction of the clock genes Per1 and Per2 in the SCN (Mendoza et al 2011). Moreover, it has been shown that genetically obese 232:3 mice (ob/ob, leptin deficiency; db/db, lacking the leptin receptor) exhibit disturbances in their peripheral clocks (Ando et al 2011, Grosbellet et al 2016.…”
Section: Leptinmentioning
confidence: 99%
“…In humans, acute HFD feeding results in lower 24-h leptin (Havel et al 1999), whereas hyperleptinemia and changes in leptin rhythmicity are observed in obese subjects in accordance with increased fat mass (Considine et al 1996, Rosenbaum et al 1996, van Dielen et al 2002. Despite having no direct effect on locomotor activity, leptin can induce PER expression in the SCN of female mice and potentiate the phase-shifting effects of light in these animals (Mendoza et al 2011). Ex vivo, leptin stimulation can reset the phase of the SCN clock (Prosser & Bergeron 2003).…”
Section: Leptin and Adiponectinmentioning
confidence: 99%